Importance of Donor Chondrocyte Viability for Osteochondral Allografts. (May 2016) - Cook, James L.; Stannard, James P.; Stoker, Aaron M.; Bozynski, Chantelle C.; Kuroki, Keiichi; Cook, Cristi R.; Pfeiffer, Ferris M.
Background: Osteochondral allograft (OCA) transplantation provides a biological treatment option for functional restoration of large articular cartilage defects in multiple joints. While successful outcomes after OCA transplantation have been linked to viable donor chondrocytes, the importance of donor cell viability has not been comprehensively validated. Purpose: To use a canine model to determine the importance of donor chondrocyte viability at the time of implantation with respect to functional success of femoral condylar OCAs based on radiographic, gross, cell viability, histologic, biochemical, and biomechanical outcome measures. Study Design: Controlled laboratory study. Methods: After approval was obtained from the institutional animal care and use committee, adult female dogs (N = 16) were implanted with 8-mm cylindrical OCAs from male dogs in the lateral and medial femoral condyles of 1 knee. OCAs were preserved for 28 or 60 days after procurement, and chondrocyte viability was quantified before implantation. Two different storage media, temperatures, and time points were used to obtain a spectrum of percentage chondrocyte viability at the time of implantation. A successful outcome was defined as an OCA that was associated with graft integration, maintenance of hyaline cartilage, lack of associated cartilage disorder, and lack of fibrillation, fissuring, or fibrous tissue infiltration of the allograft based on subjective radiographic, gross, and histologic assessments at 6 months after implantation. Results: Chondrocyte viability ranged from 23% to 99% at the time of implantation. All successful grafts had >70% chondrocyte viability at the time of implantation, and no graft with chondrocyte viability <70% was associated with a successful outcome. Live-dead stained sections and histologic findings with respect to cell morphological features suggested that successful grafts were consistently composed of viable chondrocytes in lacunae, while grafts that were not successful were composed of nonviable chondrocytes with infiltration of fibroblasts from the surrounding recipient tissues. In situ polymerase chain reaction (fluorescence in situ hybridization [FISH]) assays were performed in an attempt to distinguish donor (male) cells from recipient (female) cells. Unfortunately, this technique was exceptionally difficult to perform on intact articular cartilage sections, and consistent, repeatable data could not be obtained from this testing. However, the data did support histologic and live-dead data, which strongly suggested that successful grafts retained viable donor (male) chondrocytes and unsuccessful grafts degraded and were replaced by fibrous tissue populated with recipient (female) fibroblasts. Conclusion: Viable chondrocytes in OCAs at the time of transplantation are primarily responsible for maintenance of donor articular cartilage health in the long term. Clinical Relevance: Optimizing chondrocyte viability in all aspects of OCA transplantation—including procurement, processing, storage, transportation, and surgical implantation—needs to be a primary focus for OCA clinical use.